First records of micromycetes Peronospora violacea Berk. in Belarus - Khramtsov, Alexander K. (Experimental Biology and Biotechnology, 2017)
The data concerning the first findings of the micromycetes Peronospora violacea Berk. (Peronosporaceae, Peronosporales, Oomycetes, Oomycota, Chromista) within Belarus is presented. This species is an obligate parasitic pseudofungus and affects the flowers of family Dipsacaceae Juss. causing downy mildew. We supply data about distribution of this micromycetes in Europe, its chorologic features, host-plants and symptoms of downy mildew on flowers. Micromycetes P. violacea is found on the flowers of Knautia arvensis (L.) Coult. in two Belarusian locations. We provide a brief morphological description of this pathogen based on the assessing of collected samples. The herbarium samples that are referred to in our work and serve as the grounds for this article are retained in Belarusian State University Herbarium (MSKU). The results of this research work extend our knowledge of morphometric characteristics and distribution of pseudofungus P. violacea and might be taken into consideration when compiling the inventory of Belarusian mycobiota. The information about possible host-plants P. violacea in Belarus is valuable for the detection of diseased plants and development of measures for protection cultivated Dipsacaceae plants from downy mildew of flowers.